Stories of Enrique Otero D’costa on The War of the Thousand Days (2015)
This article continuous as conductive element Enrique Otero D’Costa’s work, Dianas tristes and Montañas de Santander, through which you can see the doom and death as essential elements of everyday life during the War of a Thousand Days. However, in the poetry of Otero D’Costa is no space to highlight feelings like friendship and brotherly love among the bloodiest confrontation lived in Colombia in the late nineteenth century and early twentieth century.